The Effect of Accounting Conservatism on Managerial Ability : an Applied Study on A Sample of Banks listed on The Iraqi Stock Exchange (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract:                The research aims to study the effect of accounting conservatism on the managerial ability of banks listed on the Iraqi Stock Exchange, To achieve the research goal, the researchers relied on collecting data on the practical side of the annual reports of the banks in the research sample for the period (2019 - 2021) with (3) observations for each bank, The researchers reached a set of conclusions, the most important of which is that the units’ practice of accounting conservatism affects the managerial ability of the banks’ authorized managers,  Their managerial ability increases with the increase in these banks’ practice of conservatism, and according to the statistical results, there is a correlation between the level of accounting conservatism and the degree of managerial ability of the executive directors of the banks in the research sample.